Prevalence of Candida species in onychomycosis at a Tertiary Care Hospital Karachi - Shahzad Haider, Kiran Pervaiz, Komal Noor, Madiha Fayyaz, Sajid Nazir, Lubna Ehtizaz (Journal of Rawalpindi Medical College, 2021)
Objective: This study was designed to determine the frequency of Candida in clinically diagnosed cases of onychomycosis. Study Design: It was a cross-sectional study. Setting: It was conducted in the Department of Microbiology, BMSI, JPMC, Karachi, in a period of one year with the collaboration of the Department of Dermatology, JPMC, Karachi. Materials and Methods: A total of 328 clinical samples have been collected. The fungal isolates were identified according to standard microbiological procedures. Samples were processed for primary screening microscopic test by KOH 20% (potassium hydroxide solution) wet mount. Processing for mycological culture was done by using Sabouraud’s dextrose agar (cycloheximide and chloramphenicol), without antibiotics and Dermatophytes test medium. Candida species identification will be achieved through the commercial test of the API ID 32C system. Results: Prevalence of fungal species that isolated from the 328 samples, 14.33% were dermatophytes, 6.40% were non-dermatophytes mould, 23.70% were Candida, 4.87% were mixed growth and 50.30% were negative for growth. Among the 16 mixed isolates, 15 were Candida species, accounting for a total of 28.4% Candida isolates. Out of 93, Candida albicans were 52.68%. Of the 47.32%, 26.88%, 11.82%, 4.30%, 2.15% and1.07%, Candida non albicans C. tropicalis C. parapsilosis, C. glabrata, C. krusei, C. guilliermondii, and Candida utilis respectively. Conclusion: A significant number of onychomycosis cases result from the Candida spp. and Candida albicans were the main species. However, Candida non-albicans species are emerging in onychomycosis. In this manner, legitimate conclusion of the pathogens of onychomycosis is vital for focused treatment.